Legal Response to Consumer Protection Risks in The Information Technology Era - Dwi Arianti, Zahra; Prastyanti, Rina Arum (IJBLE Scientific Publications Community Inc., 2025)
In the rapidly evolving digital era, consumers are increasingly exposed to a variety of new threats that were previously unimaginable, ranging from the misuse of personal data to the opaque manipulation of digital behavior through algorithms and persuasive design. These phenomena signal a profound shift in the consumer landscape, where legal certainty and traditional enforcement mechanisms may no longer suffice. This article critically analyzes whether current consumer protection laws, especially within the Indonesian context, are adequately equipped to address the contemporary risks posed by information technology. By employing a normative juridical approach and enriched with comparative legal analysis, the study draws upon key philosophical foundations from thinkers such as Satjipto Rahardjo, Gustav Radbruch, Aristotle, John Rawls, Ulrich Beck, and Nonet & Selznick. These theoretical perspectives are used to frame a vision of a more responsive, just, and forward-looking legal system. Through comparisons with regulatory frameworks in the European Union, the United States (notably California), Singapore, and Malaysia, this paper proposes that Indonesia's legal architecture must evolve not merely to react but to anticipate and shape digital transformations in ways that ensure fairness, transparency, and inclusivity. Such a legal model must be both normatively grounded and practically agile to protect consumers in an increasingly borderless and algorithm-driven marketplace.